The Balance between Plasmacytoid DC versus Conventional DC Determines Pulmonary Immunity to Virus Infections - Smit, Joost J. (Public Library of Science, 2008)
BACKGROUND: Respiratory syncytial virus (RSV) infects nearly all infants by age 2 and is a leading cause of bronchiolitis. RSV may employ several mechanisms to induce immune dysregulation, including dendritic cell (DC) modulation during the immune response to RSV. METHODS AND FINDINGS: Expansion of cDC and pDC by Flt3L treatment promoted an anti-viral response with reduced pathophysiology characterized by decreased airway hyperreactivity, reduced Th2 cytokines, increased Th1 cytokines, and a reduction in airway inflammation and mucus overexpression. These protective aspects of DC expansion could be completely reversed by depleting pDCs during the RSV infection. Expansion of DCs by Flt3L treatment enhanced in CD8+ T cell responses, which was reversed by depletion of pDC. CONCLUSIONS: These results indicate that a balance between cDC and pDC in the lung and its lymph nodes is crucial for the outcome of a pulmonary infection. Increased pDC numbers induced by Flt3L treatment have a protective impact on the nature of the overall immune environment.